Medically Necessary Orthopaedic Surgery During the COVID-19 Pandemic: Safe Surgical Practices and a Classification to Guide Treatment. (15th July 2020) - Service, Benjamin C.; Collins, Andrew P.; Crespo, Antonio; Couto, Patricia; Gupta, Sunny; Avilucea, Frank; Kupiszewski, Stanley; Langford, Joshua; Lewellyn, Brett; Petrie, Jeffrey; Zumsteg, Justin W.; Zeini, Ibrahim M.; et al.
Abstract : Background: Coronavirus disease 2019 (COVID-19) has rapidly evolved as a viral pandemic. Countries worldwide have been affected by the recent outbreak caused by the SARS (severe acute respiratory syndrome)-CoV-2 virus. As with prior viral pandemics, health-care workers are at increased risk. Orthopaedic surgical procedures are common in health-care systems, ranging from emergency to elective procedures. Many orthopaedic surgical procedures are life or limb-saving and cannot be postponed during the COVID-19 pandemic because of potential patient harm. Our goal is to analyze how orthopaedic surgeons can perform medically necessary procedures during the pandemic and to help guide decision-making perioperatively. Methods: We performed a review of the existing literature regarding COVID-19 and prior viral outbreaks to help guide clinical practice in terms of how to safely perform medically necessary orthopaedic procedures during the pandemic for both asymptomatic patients and high-risk (e.g., COVID-19-positive) patients. We created a classification system based on COVID-19 positivity, patient health status, and COVID-19 prevalence to help guide perioperative decision-making. Results: We advocate that only urgent and emergency surgical procedures be performed. By following recommendations from the American College of Surgeons, the Centers for Disease Control and Prevention, and the recent literature, safe orthopaedic surgery and perioperative care can be performed. Screening measures are needed for patients and perioperative teams. Surgeons and perioperative teams at risk for contracting COVID-19 should use appropriate personal protective equipment (PPE), including N95 respirators or powered air-purifying respirators (PAPRs), when risk of viral spread is high. When preparing for medically necessary orthopaedic procedures during the pandemic, our classification system will help to guide decision-making. A multidisciplinary care plan is needed to ensure patient safety with medically necessary orthopaedic procedures during the COVID-19 pandemic. Conclusions: Orthopaedic surgery during the COVID-19 pandemic can be performed safely when medically necessary but should be rare for COVID-19-positive or high-risk patients. Appropriate screening, PPE use, and multidisciplinary care will allow for safe medically necessary orthopaedic surgery to continue during the COVID-19 pandemic. Level of Evidence: Prognostic Level V . See Instructions for Authors for a complete description of levels of evidence.